2019
DOI: 10.1111/ijcs.12544
|View full text |Cite
|
Sign up to set email alerts
|

Investigating consumers’ green values and food‐related behaviours in Turkey

Abstract: This study sets out to examine the influence of consumers’ green values on food‐related behaviours. Data were collected from a random sample of 385 consumers in Izmir, Turkey via face‐to‐face interviews. Factor analysis was conducted to identify the underlying dimensions that capture the meaning of green values, which affect shopping, cooking and eating behaviours of consumers. A composite variable that represents consumers’ perception of green values was created to classify consumers into two segments labelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Many scholars have shown that environmental value has an important impact on consumers' environmental attitude, which then has a positive impact on green purchasing behavior (Cheung & To, 2019; Corraliza & Berenguer, 2000; Gunden, Atis, & Salali, 2020). Marketers should be aware that when the environmental values of consumers are weak, the functionality of a product is critical for making a purchase, whereas when the values are strong, consumer behavior is more influenced by the environmental impact of the product (Schuitema & Groot, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many scholars have shown that environmental value has an important impact on consumers' environmental attitude, which then has a positive impact on green purchasing behavior (Cheung & To, 2019; Corraliza & Berenguer, 2000; Gunden, Atis, & Salali, 2020). Marketers should be aware that when the environmental values of consumers are weak, the functionality of a product is critical for making a purchase, whereas when the values are strong, consumer behavior is more influenced by the environmental impact of the product (Schuitema & Groot, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to this study, demographic characteristics (such as age, gender, education level, employment type, income level, family structure, housing type, and number of private cars) are among the important internal contextual conditions to explain the “intention–behavior” gap. Therefore, when formulating green marketing programs, enterprises should focus on the development of customized marketing programs considering gender, age, marital status, education level, income status, family structure, housing type, and other factors, rather than the general “one size fits all” standardized marketing scheme (Gunden et al, 2020).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study populations ranged from n = 73 to n = 3085 participants aged between 18 years and 85+ years. The majority of studies included both male and female participants (n = 28) [13,[26][27][28][32][33][34][35][36][37][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54], however one had females only [38], and one did not specify sex or gender [43]. The studies included were from a range of countries such as Australia (n = 4) [13,33,47,54], Chile (n = 3) [48][49][50], and Croatia (n = 2) [32,42], and were published in a range of journals from public health, nutrition, and social marketing disciplines.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n = 22) recruited adult volunteers or did not specify whether participants were incentivised to complete the study [13,26,28,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]51,52], five studies paid or incentivised participants on completion of the study [27,47,53,54], and three studies recruited student samples from universities without stating whether they were incentivised or volunteers [48][49][50]. Inclusion criteria for the studies were variable, the most common criteria requiring participants to be at least 18 years old [26,34,35,37,42,44,46,47,[51][52][53][54].…”
Section: Resultsmentioning
confidence: 99%